Localizing Literature: The Use of Non-Native English Reading Sources - Radik Darmawan; Santosa Santosa (English Education : English Journal for Teaching and Learning, 2022)
The present study examined the English literature students’ perception on the use of local sources, which were used as alternative reading sources. Despite being insufficient in terms of grammatical accuracy, naturalness of the text, and the poor layout, these local sources can also improve the students’ understanding toward the reading materials. Besides, the simplified vocabulary and grammar found in the text can also help the less able learners to understand the learning sources easier. The main advantages for the students identified in the study were actually the affordability and the accessibility of the learning materials. However, the students also suggest that these local sources should be continously improve so that these materials can be more interesting for the students to read. Keywords: Localizing literature: The use, teaching media, English reading sources, higher education context